Fluctuation dynamics of bilayer vesicles with intermonolayer sliding: Experiment and theory. (January 2015) - Mell, Michael; Moleiro, Lara H.; Hertle, Yvonne; López-Montero, Iván; Cao, Francisco J.; Fouquet, Peter; Hellweg, Thomas; Monroy, Francisco
Highlights: Fluctuation dynamics of DMPC vesicles studied with NSE and flickering spectroscopy. The static spectrum is dominated by bending energy but depends on the vesicle radius. The autocorrelation function reveals a bimodal relaxation compatible with the existence of a hybrid dilation–curvature mode superposed to the bending mode. A perturbation bimodal theory predicts a linear dependence with radius for the amplitude of the hybrid mode. Combined NSE + flickering experimental data agree with the bimodal theory proposed in this work. Abstract: The presence of coupled modes of membrane motion in closed shells is extensively predicted by theory. The bilayer structure inherent to lipid vesicles is suitable to support hybrid modes of curvature motion coupling membrane bending with the local reorganization of the bilayer material through relaxation of the dilatational stresses. Previous experiments evidenced the existence of such hybrid modes facilitating membrane bending at high curvatures in lipid vesicles [Rodríguez-García, R., Arriaga, L.R., Mell, M., Moleiro, L.H., López-Montero, I., Monroy, F., 2009. Phys. Rev. Lett. 102, 128201.]. For lipid bilayers that are able to undergo intermonolayer sliding, the experimental fluctuation spectra are found compatible with a bimodal schema. The usual tension/bending fluctuations couple with the hybrid modes in a mechanical interplay, which becomes progressively efficient with increasing vesicle radius, to saturate at infinity radius into the behavior expected for a flat membrane. Grounded on the theory of closed shells, we propose an approximated expression of the bimodal spectrum, which predicts the observed dependencies on the vesicle radius. The dynamical features obtained from the autocorrelation functions of the vesicle fluctuations are found in quantitative agreement with the proposed theory.